8C.09: A CENTRAL ILIAC ARTERIOVENOUS ANASTOMOSIS RESULTS IN DURABLE AND SUBSTANTIAL BLOOD PRESSURE REDUCTION IN A WOMAN WITH UNCONTROLLED HYPERTENSION AND MULTIPLE DRUG INTOLERANCES. (June 2015) - Saxena, M.; Collier, D.; Jain, A.; Knight, C.; Mathur, A.; Sobotka, P.; Lobo, M.
Abstract : Objective: Intolerance of antihypertensive medications is a major cause of non-adherence to pharmacotherapy leading to poor blood pressure control in the hypertensive population. We investigated the role of a central iliac arteriovenous (AV) anastomosis in a woman with uncontrolled hypertension due to multidrug intolerances. Design and method: A sixty-one year old Caucasian female with long-standing poorly-controlled hypertension was referred with multiple drug intolerances. She was unable to take Amlodipine, Nifedipine, Lercanidipine, Lisinopril, Candesartan, Bendroflumethiazide, Indapamide, Spironolactone, Amiloride, Doxazosin, Bisoprolol due to unacceptable side effects. After multiple pharmacotherapeutic attempts over a one year period, she could only tolerate Nebivolol 2.5 mg daily, liquid Nifedipine solution 16 mg twice daily and one quarter Glyceryl trinitrate (GTN) 5 mg transdermal patch daily. Despite this BP control remained suboptimal and she was offered treatment with the ROX coupler device having declined renal denervation for personal reasons. Results: At baseline the office BP (OBP) was 165/92 mmHg and 24 hour ambulatory BP (ABP) confirmed suboptimal control with an average daytime mean of 158/83 mmHg, nocturnal mean 126/65 mmHg. At 6 months after creation of a right-sided iliac AV anastomosis, OBP was reduced by 24/21 mmHg), and 24 hour ABP daytime average by 14/12 mmHg. At this point her BP was sufficiently well controlled to allow discontinuation of the nebivolol and GTN patch with no further change in BP at 1 year follow up. Baseline and 6 month echocardiograms both showed mild LVH with no change in ventricular wall thickness or ejection fraction. There was no significant change in renal function post-AV anastomosis. Right heart catheterisation at 6 months showed normal pressure in the right heart and pulmonary system. Conclusions: This is the first report of a patient with multiple drug intolerances and uncontrolled hypertension undergoing treatment with a central iliac AV anastomosis resulting in early and sustained OBP lowering to target levels and reduction in daytime mean ABP. This novel therapy appears to target mechanical properties of the circulation and may be of benefit in the management of patients with uncontrolled hypertension including those with multiple medication intolerances.